Assessment of dimensions of mandibular condyles and their correlation with jaw movements in rheumatoid arthritis patients - Jalal, Ranj Adil; Ahmed, Khadija Muhamad; Saeed, Shahla Muhamad (Sulaimani Journal for Pure and Applied Sciences, 2023)
Objectives: The aim of this study is to assess the condylar dimensions in Rheumatoid Arthritis (RA) patients and compare them to condylar dimensions of healthy persons and try to find out correlations between dimensional condylar changes and jaw movements in RA patients. Methods: This case-control study was performed on 40 RA patients with ten healthy adults (control cases). Clinical examination with Cone Beam Computerized Tomography (CBCT) was done for participants. Independent and paired t-tests with correlation coefficient tests were used for data analysis by the SPSS program. Results: There was a significant difference between RA and controls regarding the means of their unassisted and assisted maximum mouth opening and the mean of right lateral jaw excursion also. The mean condylar length in RA patients was 6.88 mm while in control cases was 7.61, and the mean condylar width in RA was 16.77 and in controls was 16.53 mm, and the mean condylar height was 18.02 mm in RA and 21.14 mm in controls without significant difference between both groups. There was a positive correlation between the condylar dimensions and the jaw movements. Conclusions: Condylar height and width were decreased in RA patients in comparison to the control group, indicating bony changes in the upper condylar surface. In addition, RA patients have decreased range of jaw movements like mouth opening, which might result from bony changes and reduction in condylar dimensions.
Keywords: Rheumatoid Arthritis; CBCT; TMJ; Condyle